Naturalizing values: organisms and species - Rolston, Holmes, 1932-2025, author; Wadsworth, publisher (Colorado State University. Libraries, 2001)
Philosophers are seem unable and unwilling to naturalize value. But values are deeply embedded in evolutionary and ecological natural history. Biologists are regularly discovering such values; survival value is a key to natural selection and adapted fit. Nevertheless, most philosophers insist that value is anthropocentric, allowing only dispositional value to nature, also value where there is sentient life. These psychological accounts are incomplete. This is evidenced in non-sentient organisms, in species lines, and in genetic knowledge. Unless we naturalize values, we face an epistemic and axiological crisis.
Paper given at American Philosophical Association, Washington, DC, December 1998.
Keywords: biocentric values; axiology; metaphysics; epistemology; ethics; values; naturalism; dragonflies; leaf stomata; bacterial clocks; genomes